2016
DOI: 10.3892/ijo.2016.3711
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management for non-functional pancreatic neuroendocrine neoplasms with synchronous liver metastasis: A consensus from the Chinese Study Group for Neuroendocrine Tumors (CSNET)

Abstract: Pancreatic neuroendocrine neoplasms (p-NENs) are slowly growing tumors with frequent liver metastasis. There is a variety of approaches to treat non-functional p-NENs with synchronous liver metastasis (LM) which complicates the determination of optimal treatment. Based on updated literature review, we discussed the treatment strategy determinants for p-NEN with LM. According to the resectability of primary tumor, the WHO 2010 grade classification and the radiological type of liver metastasis, the CSNET group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 89 publications
(112 reference statements)
0
30
0
Order By: Relevance
“…14,17,18 In turn, the presence of unresectable primary NETs and/or extrahepatic metastasis are still considered a contraindication to surgery by many clinicians. 11,19 However, aggressive onco-surgery has been increasingly advocated, even in the presence of advanced metastatic disease. 20,21 The current study was important as it specifically defined the outcomes of patients with advanced NF-NELM who had unresected primary NETs, as well as extrahepatic metastasis using a large, international, multiinstitutional database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,17,18 In turn, the presence of unresectable primary NETs and/or extrahepatic metastasis are still considered a contraindication to surgery by many clinicians. 11,19 However, aggressive onco-surgery has been increasingly advocated, even in the presence of advanced metastatic disease. 20,21 The current study was important as it specifically defined the outcomes of patients with advanced NF-NELM who had unresected primary NETs, as well as extrahepatic metastasis using a large, international, multiinstitutional database.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Traditionally, the presence of unresectable primary disease and/or extrahepatic metastatic disease was considered advanced NELM. 10 While some investigators have recommended against resection of NELM in the setting of advanced disease, 11 other data have supported surgical debulking as a reasonable treatment of NELM that has yielded improved long-term survival. 12 As most patients with NELM die of liver failure due to intrahepatic tumor progression rather than the primary tumor or extrahepatic disease, liver resection may have a role, even in the setting of advanced disease.…”
mentioning
confidence: 99%
“…Further studies have identified distinct biological differences between limited metastatic lesions and widely disseminated disease for multiple tumor types, including pancreatic cancer[ 13 - 15 ]. Radical surgery to treat both primary and metastatic sites has been accepted and conducted for an increasing number of tumor types[ 16 - 18 ]. Thus, pancreatic cancer patients with few liver metastases may benefit from aggressive surgical approaches.…”
Section: Perspectivementioning
confidence: 99%
“…G3 pNETs are well known for their aggressiveness and poor response to major treatment strategies, including surgery (26). Considering the differing management strategy between G1, G2 and G3 pNETs in clinical practice, the aberrant elevation of CA19-9 may serve as an indication of G3 pNETs for clinicians (26).…”
Section: Discussionmentioning
confidence: 99%